2017
DOI: 10.1021/acsomega.7b01046
|View full text |Cite
|
Sign up to set email alerts
|

Direct Realization of Complete Conversion and Agglomeration Dynamics of SnO2 Nanoparticles in Liquid Electrolyte

Abstract: The conversion reaction is important in lithium-ion batteries because it governs the overall battery performance, such as initial Coulombic efficiency, capacity retention, and rate capability. Here, we have demonstrated in situ observation of the complete conversion reaction and agglomeration of nanoparticles (NPs) upon lithiation by using graphene liquid cell transmission electron microscopy. The observation reveals that the Sn NPs are nucleated from the surface of SnO 2 , followed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…Through further analysis using EELS spectra (Fig. 8c), it has been confirmed that the SEI layer was formed, having a peak at 61 and 69 eV, in accordance with the previous literature (Cheong et al, 2016; Chang et al, 2017). Formation of Li 2 O was also confirmed by EELS spectra (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Through further analysis using EELS spectra (Fig. 8c), it has been confirmed that the SEI layer was formed, having a peak at 61 and 69 eV, in accordance with the previous literature (Cheong et al, 2016; Chang et al, 2017). Formation of Li 2 O was also confirmed by EELS spectra (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Structural integrity is maintained during the lithiation-induced phase transitions, so the growth of Sn crystals nucleated from SnO 2 as a result of the conversion reaction can be visualized well, compared with SnO 2 nanowires which may exhibit larger volume changes. It has been demonstrated in the recent literature (Chang et al, 2017) that the conversion reaction of SnO 2 inside the GLCs is similar to the conversion reaction pathway in an electrochemical cell, and the conversion reaction of various metal oxides can be visualized inside the GLC. As demonstrated in a scanning electron microscopy image in Figure 2a, a hollow SnO 2 NT consists of many SnO 2 nanograins.…”
Section: Resultsmentioning
confidence: 93%
“…In Situ TEM Sample Preparation and Characterization : TEM sample was prepared by dropping NaF (or LiF) particles and CuS nanoplates on a graphene coated holey carbon Au grid (300 mesh, SPI), which was prepared by direct transfer method . NaF (or LiF) was used to generate metallic Na (or Li) from NaF (or LiF).…”
Section: Methodsmentioning
confidence: 99%
“…[33,34] NaF (or LiF) was used to generate metallic Na (or Li) from NaF (or LiF). [33,34] NaF (or LiF) was used to generate metallic Na (or Li) from NaF (or LiF).…”
Section: Wwwadvancedsciencecommentioning
confidence: 99%
“…The predominant reason the actual capacities of SnO 2 are lower than the theoretical value is the poor reversibility of the conversion reaction (Equation ), which had long been considered an irreversible reaction due to the high energy barrier (i.e., ≈602 kJ mol −1 ) of the reaction from Sn and Li 2 O to SnO 2 . The low conversion reaction reversibility results in low initial Coulombic efficiency (CE, ≈52%) and gradual capacity degeneration during cycling of bulk SnO 2 .…”
Section: Introductionmentioning
confidence: 99%